Stimulation of terrestrial ecosystem carbon storage by nitrogen addition: a meta-analysis - Yue, Kai; Peng, Yan; Peng, Changhui; Yang, Wanqin; Peng, Xin; Wu, Fuzhong (Scientific Reports, 2016)
Abstract Elevated nitrogen (N) deposition alters the terrestrial carbon (C) cycle, which is likely to feed back to further climate change. However, how the overall terrestrial ecosystem C pools and fluxes respond to N addition remains unclear. By synthesizing data from multiple terrestrial ecosystems, we quantified the response of C pools and fluxes to experimental N addition using a comprehensive meta-analysis method. Our results showed that N addition significantly stimulated soil total C storage by 5.82% ([2.47%, 9.27%], 95% CI, the same below) and increased the C contents of the above- and below-ground parts of plants by 25.65% [11.07%, 42.12%] and 15.93% [6.80%, 25.85%], respectively. Furthermore, N addition significantly increased aboveground net primary production by 52.38% [40.58%, 65.19%] and litterfall by 14.67% [9.24%, 20.38%] at a global scale. However, the C influx from the plant litter to the soil through litter decomposition and the efflux from the soil due to microbial respiration and soil respiration showed insignificant responses to N addition. Overall, our meta-analysis suggested that N addition will increase soil C storage and plant C in both above- and below-ground parts, indicating that terrestrial ecosystems might act to strengthen as a C sink under increasing N deposition.

Degradation of lignin and cellulose during foliar litter decomposition in an alpine forest river - Yue, Kai; Peng, Changhui; Yang, Wanqin; Peng, Yan; Zhang, Chuan; Huang, Chunping; Wu, Fuzhong (Ecosphere, 2016)
Abstract Lignin and cellulose are thought to be critical factors that affect the rate of litter decomposition; however, few data are available on their degradation dynamics during litter decomposition in lotic ecosystems, such as forest rivers, where litter can decompose much more rapidly than in terrestrial ecosystems. We studied the degradation of lignin and cellulose in the foliar litter of four dominant riparian species (willow: Salix paraplesia ; azalea: Rhododendron lapponicum ; cypress: Sabina saltuaria ; and larch: Larix mastersiana ) in an alpine forest river. Over an entire year's incubation, litter lignin and cellulose degraded by 14.7–100% and 57.7–100% of their initial masses, respectively, depending on litter species. Strong degradations of lignin and cellulose occurred in the prefreezing period (i.e., the first 41 d) during litter decomposition, and the degradation rate was the highest among all the decomposition periods regardless of litter species. Litter species, decomposition period, and environmental factors such as temperature and nutrient availability showed significant influences on lignin and cellulose degradation rates. Compared with previously reported data regarding the dynamics of lignin and cellulose during litter decomposition in terrestrial ecosystems, our results suggest that lignin and cellulose can be degraded much more rapidly in lotic ecosystems, indicating that the traditionally used two‐phased model for the dynamics of lignin in decomposing litter may not be suitable in lotic ecosystems.

Effects of three global change drivers on terrestrial C:N:P stoichiometry: a global synthesis - Yue, Kai; Fornara, Dario A.; Yang, Wanqin; Peng, Yan; Li, Zhijie; Wu, Fuzhong; Peng, Changhui (Global Change Biology, 2017)
Abstract Over the last few decades, there has been an increasing number of controlled‐manipulative experiments to investigate how plants and soils might respond to global change. These experiments typically examined the effects of each of three global change drivers [i.e., nitrogen (N) deposition, warming, and elevated CO 2 ] on primary productivity and on the biogeochemistry of carbon (C), N, and phosphorus (P) across different terrestrial ecosystems. Here, we capitalize on this large amount of information by performing a comprehensive meta‐analysis (>2000 case studies worldwide) to address how C:N:P stoichiometry of plants, soils, and soil microbial biomass might respond to individual vs. combined effects of the three global change drivers. Our results show that (i) individual effects of N addition and elevated CO 2 on C:N:P stoichiometry are stronger than warming, (ii) combined effects of pairs of global change drivers (e.g., N addition + elevated CO 2 , warming + elevated CO 2 ) on C:N:P stoichiometry were generally weaker than the individual effects of each of these drivers, (iii) additive interactions (i.e., when combined effects are equal to or not significantly different from the sum of individual effects) were more common than synergistic or antagonistic interactions, (iv) C:N:P stoichiometry of soil and soil microbial biomass shows high homeostasis under global change manipulations, and (v) C:N:P responses to global change are strongly affected by ecosystem type, local climate, and experimental conditions. Our study is one of the first to compare individual vs. combined effects of the three global change drivers on terrestrial C:N:P ratios using a large set of data. To further improve our understanding of how ecosystems might respond to future global change, long‐term ecosystem‐scale studies testing multifactor effects on plants and soils are urgently required across different world regions.

Foliar litter decomposition in an alpine forest meta-ecosystem on the eastern Tibetan Plateau - Yue, Kai; Yang, Wanqin; Peng, Changhui; Peng, Yan; Zhang, Chuan; Huang, Chunping; Tan, Yu; Wu, Fuzhong (Science of The Total Environment, 2016)

Individual and combined effects of multiple global change drivers on terrestrial phosphorus pools: A meta-analysis - Yue, Kai; Yang, Wanqin; Peng, Yan; Peng, Changhui; Tan, Bo; Xu, Zhenfeng; Zhang, Li; Ni, Xiangyin; Zhou, Wei; Wu, Fuzhong (Science of The Total Environment, 2018)

Immediate and carry-over effects of increased soil frost on soil respiration and microbial activity in a spruce forest - Yang, Kaijun; Peng, Changhui; Peñuelas, Josep; Kardol, Paul; Li, Zhijie; Zhang, Li; Ni, Xiangyin; Yue, Kai; Tan, Bo; Yin, Rui; Xu, Zhenfeng (Soil Biology and Biochemistry, 2019)

Globally limited individual and combined effects of multiple global change factors on allometric biomass partitioning - Peng, Yan; Fornara, Dario A.; Yue, Kai; Peng, Xin; Peng, Changhui; Wu, Qiqian; Ni, Xiangyin; Liao, Shu; Yang, Yusheng; Wu, Fuzhong; Peñuelas, Josep (Global Ecology and Biogeography, 2022)
Abstract Aim Plant biomass allocation reflects the distribution of photosynthates among different organs in response to changing environmental conditions. Global change influences plant growth across terrestrial ecosystems, but impacts of individual and combined multiple global change factors (GCFs) on plant biomass allocation at the global scale are unclear. Location Global. Time period Contemporary. Major taxa studied Plants in terrestrial ecosystems. Methods We conducted a meta‐analysis of data comprising 4,180 pairwise observations to assess individual and combined effects of nitrogen addition (N), warming (W), elevated CO 2 (C), irrigation (I), and drought (D) on plant biomass allocation based on the ‘ratio‐based optimal partitioning’ and ‘isometric allocation’ hypotheses. Results We found that (a) ratio‐based plant biomass fractions of different organs were only minimally affected by individual and combined effects of the studied GCFs; (b) combined effects of two‐factor pairs of GCFs on plant biomass allocation were commonly additive, rather than synergistic or antagonistic; (c) moderator variables influenced, but seldom changed the direction of individual and combined effects of GCFs on plant biomass allocation; and (d) neither individual nor combined effects of the studied GCFs altered allometric relationships among different organs, indicating that patterns of plant biomass allocation under the environmental stress conditions exerted by the multiple GCFs were better explained by the isometric allocation rather than the ratio‐based optimal partitioning hypothesis. Main conclusions Our results show consistent patterns of allometric plant biomass partitioning under effects of multiple GCFs and provide evidence of an isometric plant biomass allocation trajectory in response to global change perturbations. These findings improve our understanding and prediction of terrestrial vegetation responses to future global change scenarios.

Climate warming accelerates carbon release from foliar litter—A global synthesis - Chen, Zihao; Ni, Xiangyin; Patoine, Guillaume; Peng, Changhui; Yue, Kai; Yuan, Ji; Wu, Qiuxia; Eisenhauer, Nico; Guerra, Carlos A.; Bol, Roland; Wu, Fuzhong; Wang, G. Geoff (Global Change Biology, 2024)
Abstract With over one‐third of terrestrial net primary productivity transferring to the litter layer annually, the carbon release from litter serves as a crucial valve in atmospheric carbon dioxide concentrations. However, few quantitative global projections of litter carbon release rate in response to climate change exist. Here, we combined a global foliar litter carbon release dataset (8973 samples) to generate spatially explicitly estimates of the response of their residence time ( τ ) to climate change. Results show a global mean litter carbon release rate () of 0.69 year −1 (ranging from 0.09–5.6 year −1 ). Under future climate scenarios, global mean τ is projected to decrease by a mean of 2.7% (SSP 1–2.6) and 5.9% (SSP 5–8.5) during 2071–2100 period. Locally, the alleviation of temperature and moisture restrictions corresponded to obvious decreases in τ in cold and arid regions, respectively. In contract, τ in tropical humid broadleaf forests increased by 4.6% under SSP 5–8.5. Our findings highlight the vegetation type as a powerful proxy for explaining global patterns in foliar litter carbon release rates and the role of climate conditions in predicting responses of carbon release to climate change. Our observation‐based estimates could refine carbon cycle parameterization, improving projections of carbon cycle–climate feedbacks.

Global spectra of plant litter carbon, nitrogen and phosphorus concentrations and returning amounts - Yuan, Ji; Wu, Fuzhong; Peng, Changhui; Peñuelas, Josep; Vallicrosa, Helena; Sardans, Jordi; Peng, Yan; Wu, Qiqian; Li, Zimin; Heděnec, Petr; Li, Zhijie; Tan, Siyi; et al. (Journal of Ecology, 2024)
Abstract Litter decomposition is a key ecological process that determines carbon (C) and nutrient cycling in terrestrial ecosystems. The initial concentrations of C and nutrients in litter play a critical role in this process, yet the global patterns of litter initial concentrations of C, nitrogen (N) and phosphorus (P) are poorly understood. We employed machine learning with a global database to quantitatively assess the global patterns and drivers of leaf litter initial C, N and P concentrations, as well as their returning amounts (i.e. amounts returned to soils). The medians of litter C, N and P concentrations were 46.7, 1.1, and 0.1%, respectively, and the medians of litter C, N and P returning amounts were 1.436, 0.038 and 0.004 Mg ha −1 year −1 , respectively. Soil and climate emerged as the key predictors of leaf litter C, N and P concentrations. Predicted global maps showed that leaf litter N and P concentrations decreased with latitude, while C concentration exhibited an opposite pattern. Additionally, the returning amounts of leaf litter C, N and P all declined from the equator to the poles in both hemispheres. Synthesis : Our results provide a quantitative assessment of the global concentrations and returning amounts of leaf litter C, N and P, which showed new light on the role of leaf litter in global C and nutrients cycling.

Responses of nitrogen concentrations and pools to multiple environmental change drivers: A meta‐analysis across terrestrial ecosystems - Yue, Kai; Peng, Yan; Fornara, Dario A.; Van Meerbeek, Koenraad; Vesterdal, Lars; Yang, Wanqin; Peng, Changhui; Tan, Bo; Zhou, Wei; Xu, Zhenfeng; Ni, Xiangyin; Zhang, Li; et al. (Global Ecology and Biogeography, 2019)
Abstract Aim We sought to understand how the individual and combined effects of multiple environmental change drivers differentially influence terrestrial nitrogen (N) concentrations and N pools and whether the interactive effects of these drivers are mainly antagonistic, synergistic or additive. Location Worldwide. Time period Contemporary. Major taxa studied Plants, soil, and soil microbes in terrestrial ecosystems. Methods We synthesized data from manipulative field studies from 758 published articles to estimate the individual, combined and interactive effects of key environmental change drivers (elevated CO 2 , warming, N addition, phosphorus addition, increased rainfall and drought) on plant, soil, and soil microbe N concentrations and pools using meta‐analyses. We assessed the influences of moderator variables on these effects through structural equation modelling. Results We found that (a) N concentrations and N pools were significantly affected by the individual and combined effects of multiple drivers, with N addition (either alone or in combination with another driver) showing the strongest positive effects; (b) the individual and combined effects of these drivers differed significantly between N concentrations and N pools in plants, but seldom in soils and microbes; (c) additive effects of driver pairs on N concentrations and pools were much more common than synergistic or antagonistic effects across plants, soils and microbes; and (d) environmental and experimental factors were important moderators of the individual, combined and interactive effects of these drivers on terrestrial N. Main conclusions Our results indicate that terrestrial N concentrations and N pools, especially those of plants, can be significantly affected by the individual and combined effects of environmental change drivers, with the interactive effects of these drivers being mostly additive. Our findings are important because they contribute to the development of models to better predict how altered N availability affects ecosystem carbon cycling under future environmental changes.